Cell Interactions with Size-Controlled Colloidal Monolayers: Toward Improved Coatings in Bone Tissue Engineering - Walter, Teresa; Grünewald, Alina; Detsch, Rainer; Boccaccini, Aldo R.; Vogel, Nicolas (Langmuir, 2020)
The surface structure of biomaterials is of key importance to control its interactions with biological environments. Industrial fabrication and coating processes often introduce particulate nanostructures at implant surfaces. Understanding the cellular interaction with particle-based surface topologies and feature sizes in the colloidal length scale therefore offers the possibility to improve the biological response of synthetic biomaterials. Here, surfaces with controlled topography and regular feature sizes covering the relevant length scale of particulate coatings (100-1000 nm) are fabricated by colloidal templating. Using fluorescent microscopy, WST assay, and morphology analysis, results show that adhesion and attachment of bone-marrow derived murine stromal cells (ST2) are strongly influenced by the surface feature size while geometric details play an insignificant role. Quantitative analysis shows enhanced cell adhesion, spreading, viability, and activity when surface feature size decreases below 200 nm compared to flat surfaces, while larger feature sizes are detrimental to cell adhesion. Kinetic studies reveal that most cells on surfaces with larger features lose contact with the substrate over time. This study identifies colloidal templating as a simple method for creating highly defined model systems to investigate complex cell functions and provides design criteria for the choice of particulate coatings on commercial implant materials.
CRIS-Team Scopus Importer:2020-03-17

Dispersion-based, scalable fabrication of repellent superhydrophobic and liquid-infused coatings under ambient conditions - Walter, Teresa; Hein, Tamara; Weichselgartner, Matthias; Wommer, Kirsten; Aust, Martin; Vogel, Nicolas (Green Chemistry, 2022)
Superhydrophobic and liquid-infused porous coatings provide effective repellency against contaminations and ensure efficient performance of surfaces in a wide range of applications. Conventional fabrication processes of such coatings typically require fluorinated components, toxic solvents, and elevated temperatures, and therefore contribute to environmental pollution. Here, we present a dispersion-based, fluorine-free coating system that produces highly repellent surface coatings at ambient conditions. Our system is based on aqueous dispersions of a polymeric binder and hydrophobic fumed silica particles, which upon drying self-organize into a micro- and nanostructured thin film with superhydrophobic properties, characterized by a water contact angle above 150 degrees and a contact angle hysteresis below 10 degrees. An additional dispersion-based coating step allows infusing these structures with silicone oil, thus producing a lubricant-infused repellent coating mimicking the pitcher plant. Water droplets on such coatings exhibit efficient repellency properties, characterized by low sliding angles (<5 degrees) and contact angle hysteresis of water droplets (<10 degrees). Our method provides a versatile, dispersion-based toolbox to create functional, repellent coatings in a simple, scalable and environmentally benign process.

From Meso to Macro: Controlling Hierarchical Porosity in Supraparticle Powders - Sultan, Umair; Götz, Alexander; Schlumberger, Carola; Drobek, Dominik; Bleyer, Gudrun; Walter, Teresa; Loewer, Erik; Peuker, Urs Alexander; Thommes, Matthias; Spiecker, Erdmann; Apeleo Zubiri, Benjamin; Inayat, Alexandra; et al. (Small, 2023)
A drying droplet containing colloidal particles can consolidate into a spherical assembly called a supraparticle. Such supraparticles are inherently porous due to the spaces between the constituent primary particles. Here, the emergent, hierarchical porosity in spray-dried supraparticles is tailored via three distinct strategies acting at different length scales. First, mesopores (<10 nm) are introduced via the primary particles. Second, the interstitial pores are tuned from the meso- (35 nm) to the macro scale (250 nm) by controlling the primary particle size. Third, defined macropores (>100 nm) are introduced via templating polymer particles, which can be selectively removed by calcination. Combining all three strategies creates hierarchical supraparticles with fully tailored pore size distributions. Moreover, another level of the hierarchy is added by fabricating supra-supraparticles, using the supraparticles themselves as building blocks, which provide additional pores with micrometer dimensions. The interconnectivity of the pore networks within all supraparticle types is investigated via detailed textural and tomographic analysis. This work provides a versatile toolbox for designing porous materials with precisely tunable, hierarchical porosity from the meso- (3 nm) to the macroscale (≈10 µm) that can be utilized for applications in catalysis, chromatography, or adsorption.
CRIS-Team Scopus Importer:2023-04-07
Keywords: adsorption; hierarchy; porous materials; self-assembly; supraparticles; tomography

From Sticky to Slippery: Self-Functionalizing Lubricants for in Situ Fabrication of Liquid-Infused Surfaces - Chiera, Salvatore; Koch, Vanessa; Bleyer, Gudrun; Walter, Teresa; Bittner, Carina; Bachmann, Julien; Vogel, Nicolas (ACS Applied Materials and Interfaces, 2022)
Liquid-infused surfaces offer a versatile approach to create self-cleaning coatings. In such coatings, a thin film of a fluid lubricant homogeneously coats the substrate and thus prevents direct contact with a second, contaminating liquid. For stable repellency, the interfacial energies need to be controlled to ensure that the lubricant is not replaced by the contaminating liquid. Here, we introduce the concept of self-functionalizing lubricants. Functional molecular species that chemically match the lubricant but possess selective anchor groups are dissolved in the lubricant and self-adhere to the surface, forming the required surface chemistry in situ from within the applied lubricant layer. To add flexibility to the self-functionalizing concept, the substrate is first primed with a thin polydopamine base layer, which can be deposited to nearly any substrate material from aqueous solutions and retains reactivity toward electron-donating groups such as amines. The temporal progression of the in situ functionalization is investigated by ellipsometry and quartz crystal microbalance and correlated to macroscopic changes in contact angle and contact angle hysteresis. The flexibility of the approach is underlined by creating repellent coatings with various substrate/lubricant combinations. The prepared liquid-infused surfaces significantly reduce cement adhesion and provide easy-to-clean systems under real-world conditions on shoe soles.
CRIS-Team Scopus Importer:2022-04-22
Keywords: coatings; liquid-infused surfaces; polydopamine; self-cleaning; surface functionalization

Performance of environmentally friendly, liquid-infused coatings against biofouling: evaluation of macrofouling and microbially induced corrosion in freshwater environments - Walter, Teresa; Langbein, Manuela; Blenk, Patrik; Tesler, Alexander; Prado, Lucia; Bornstein, Dan; Virtanen, Sannakaisa; Castiglione, Kathrin; Vogel, Nicolas (Journal of Materials Chemistry A, 2024)
Biofouling, caused by the attachment of micro- and macroorganisms, increases the fuel consumption of ships and compromises aquatic infrastructure, especially by microbially induced corrosion. Conventional anti-fouling strategies often rely on the release of toxic substances. Liquid-infused coatings offer an alternative strategy, which has shown promising anti-fouling performance in maritime settings. In this study, we focus on freshwater systems and investigate the performance of a set of recently developed liquid-infused coatings with low environmental impact based on sustainable or non-toxic materials and energy-efficient fabrication. We combine field studies at two freshwater bodies in Bavaria, Germany with laboratory experiments focusing on corrosion and microbial attachment under controlled conditions. Our results indicate that liquid-infused coatings with low environmental impact can show a reduction in general biofouling, mussel attachment, and corrosion rates, as well as the attachment of Thiobacillus thioparus and Pseudomonas fluorescens, organisms known to cause microbially induced corrosion.<br

Sustainable Repellent Coatings Based on Renewable Drying and Nondrying Oils - Dehm, Katharina; Walter, Teresa; Weichselgartner, Matthias; Crisp, Ryan; Wommer, Kirsten; Aust, Martin; Vogel, Nicolas (Advanced Materials Interfaces, 2022)